MDM2 inhibitor APG-115 synergizes with ABT-199 to induce cell apoptosis in chronic lymphocytic leukemia - Cui, Ying; Shao, Xiaoya; Yang, Haiping; Xin, Jingyi; Liu, Yuanyuan; Zhang, Mingxiao; Sun, Chuanyue; Chen, Ge; Shen, Guomin; Meng, Xueqiong; Chen, Yixiang (Frontiers in Pharmacology, 2024)
Although clinical outcomes in chronic lymphocytic leukemia (CLL) have greatly improved with several approved small molecular inhibitors, acquired resistance does occur, leading to disease progression and eventual death. Thus, the effort to explore novel inhibitors and combination therapeutic regimens is needed. The inhibition of MDM2-p53 interaction to restore p53 function has been regarded as a potential strategy for treating different cancers. We investigated the effects of novel MDM2 inhibitor APG-115 in CLL. We found that APG-115 treatment upregulated the expression of p53, MDM2, and p21 at the mRNA and protein level. APG-115 inhibited cell proliferation, induced apoptosis, and arrested the cell cycle at G0/G1 stage. Moreover, APG-115 inhibited the expression of BCL-2, BCL-xL, and MCL-1, and suppressed the activation of AKT and ERK signaling pathways. APG-115 combined with the BCL2 inhibitor, , led to further inhibition of the expression of BCL-2 family anti-apoptotic proteins and consequently enhanced cell death. Collectively, this study demonstrates that APG-115 activates p53 and thus inhibits multiple pro-survival mechanisms, which provides a rational explanation for APG-115 efficiency in inducing cell apoptosis in CLL. The synergistic effect of APG-115 with ABT-199 suggested a potential combination application in CLL therapy.